Quality of Life in Cervical Cancer Survivors and Healthy Women: Thai Urban Population Study - Prasongvej, Pichita (Asian Pac J Cancer Prev, 2017)
BACKGROUND: To determine a baseline quality of life (QoL) in cervical cancer survivors compared to that of healthy subjects in the tertiary Thammasat University Hospital, Thailand. MATERIALS AND METHODS: The investigation was conducted at the outpatient gynecological department of Thammasat University Hospital between January and June 2016. A total of 192 women were entered into the study (97 cervical cancer survivors; 37 after radical hysterectomy (RH), 43 with concurrent chemoradiation (CRT), and 17 featuring both RH and CRT; and 95 control subjects from the same outpatient department with no history of malignancy). Participant QoL was assessed using a Thai version of the EORTC-QLQ-C30 (European Organization for Research Treatment of Cancer Quality-of-Life) and a general survey for the assessment of sociodemographic data was also conducted. RESULTS: There were significant differences in physical, role, emotional and social functions between cervical cancer survivor and control groups. Global health, fatigue, pain, appetite loss, and financial difficulties also demonstrated statistically significant variation. Cervical cancer survivors treated by RH had higher scores for emotional and social function and global health than the control group. Moreover, they had less appetite loss, fatigue and financial difficulties. However, patients treated with CRT experienced more pain than the control group. All cervical cancer survivors had lower physical function scores than the control group. CONCLUSION: Quality of life in cervical cancer survivors is better than in healthy peers in some domains. Cervical cancer survivors treated with RH may have a better QoL than healthy peers. Early detection for early stage cervical cancer remains most important because treatment in early stages does not cause lowering of the QoL.